Raman spectroscopy (RESpect) for anal intraepithelial neoplasia (AIN) lesions from HIV-serodiscordant couples - Robert Oda; Natalie Kamada; Bruce Shiramizu; Cris Milne; Anupam Misra; Tayro Acosta-Maeda (Papillomavirus Research, 2018)
Background: Anal dysplasia is a potentially chronic disease that affects HIV-seropositive and-seronegative men who have sex with men (MSM) and transgender women. Novel approaches to AIN screening could improve healthcare through access to timely care and treatment since appropriate training and equipment are currently required for screening and follow-up. To pioneer new ideas, the foundation for new technology relies on collecting data to design new tools. Recently, Raman spectroscopy (RESpect), a laser-based technology, has identified unique anal tissue fingerprints. We assessed anal tissue for RESpect phenotypes for differences in HIV-serodiscordant couples. Methods: HIV-serodiscordant couples were enrolled in a clinical study to assess anal biopsy specimens as per IRB guidelines. Anal tissue was flash-frozen and mounted onto aluminum reflective slides which were then subjected to RESpect point scans accumulations. RESpect information was processed using asymmetric least squares to baseline the data and subjected to principal component analysis (PCA). Results: To date, data from 2 couples showed that PCA distinguishes between HIV+ and HIV- individuals of the couples. In HIV+ individuals, PCA also distinguishes AIN from normal tissue. Conclusions: RESpect has shown to identify not only AIN amongst all individuals but also suggested there may be a unique HIV effect in the RESpect data from anal tissue. Further work on RESpect could provide groundbreaking information towards the design of a RESpect monitoring instrument to diagnose and follow patients for AIN. Supported in part by R21CA216830 and U54MD007584.